Variable Block-Sized Signal Dependent Transform for Video Coding - Lan, Cuiling; Xu, Ji-Zheng; Zeng, Wenjun; Shi, Guangming; Wu, Feng (IEEE Transactions on Circuits and Systems for Video Technology, 2018)
Transform, as one of the most important modules of mainstream video coding systems, seems very stable over past several decades. However, recent developments indicate that bringing more options for transform can lead to coding efficiency benefits. In this paper, we go further to investigate how the coding efficiency can be improved over the state-of-the-art by adapting transform for each block. We present a variable block-sized Signal Dependent Transforms (SDTs) design based on HEVC framework. For a coding block ranged from 44 to 3232, we collect a quantity of similar blocks from the reconstructed area and use them to derive the Karhunen-Loeve transform (KLT). We avoid sending overhead bits to denote the transform by performing the same procedure at the decoder. In this way, the transform for every block is tailored according to its statistics, to be signal dependent. To make the large block-sized SDTs feasible, we present a fast algorithm for transform derivation. Experimental results show the effectiveness of the SDTs for different block sizes, which leads to up to 23.3% bit-saving. On average, we achieve BD-rate saving of 2.2%, 2.4%, 3.3%, and 7.1% under AI-Main10, RA-Main10, RA-Main10, and LPMain10 configurations respectively, compared to the test modelc HM-12.0 of HEVC. The proposed scheme has also been adopted into the Joint Exploration Test Model (JEM) for exploration of potential future video coding standard.